Comparison of oral health outcomes and treatment recevied in intellectually disabled age groups: a comparative study - BERKEL, GÜLCAN; BAYRAM, FERİT; YILDIRIM, HATİCE SELİN (My University, 2023)
Objective: Evaluation of dental treatment of intellectually disabled (ID) people is often confusing, since the wide range of ages (children,teenagers and adults), oral health problems and concomitant diseases. There have been many studies in pediatric ID patients but little is known about the differences between age groups in children or adults. Materials-Methods: We hypothesize that children and adults with ID may have different oral health outcomes and that differences will be statistically significant. The DMFT/DMFS results, Community Periodontal Index of Treatment Needs (CPI-TN), functional occlusal pairs and units.Study population is the ID patient operated in general anesthesia between 2021-2023. All patients aged 14-65 were before general anesthesia and DMFT/DMFS, CPI, TN, occlusal unit and functional occlusal pairs data was collected. The patients were grouped according to ages on 14-24(group A) and >25 (group B) years. Study parameters were compared between this study groups. Results: The number of patient of groups A and B were 17 and 21, respectively. The values of DMFT, DMFS, occlusal unit, functional occlusion pairs, number of missing teeth and number of missing tooth surfaces in our patients were in group A and group B have no difference between before surgery, after surgery and difference after surgery-before surgery. CPI data have difference between groups. TN data have no difference between groups Conclusion: It was concluded that if patients are given tooth brushing education at an early age or if they are taken to multidisciplinary surgery, better results will be obtained in terms of the health of periodontal tissues and the treatment needs of patients will be reduced.
Keywords: General anesthesia; İntellectually disabled; Oral health